Congenital scoliosis: a narrative review and proposal of a treatment algorithm. Issue 5 (5th May 2022) - Sebaaly, Amer; Daher, Mohammad; Salameh, Bendy; Ghoul, Ali; George, Samuel; Roukoz, Sami
Abstract : Congenital scoliosis (CS) is a spinal deformity resulting from underlying spinal malformations with an incidence of 0.5–1/1000 births. CS makes up 10% of scoliotic deformities, of which 25% do not progress, 25% progress mildly and 50% need treatment depending on the age, curve characteristics and magnitude and type of anomaly. CS is associated with non-vertebral anomalies (genitourinary, musculoskeletal, cardiac, ribs anomalies, etc.) and intraspinal anomalies (syrinx and tethered cord). Imaging should include whole spine X-rays, CT scanner with reconstruction to better delineate the vertebral anomalies and MRI to visualize the neural elements. Treatment of CS in the majority of cases is non-surgical and relies on fusion techniques ( in situ fusion and hemiepiphysiodeis), resection techniques (hemiverterba resection), and growth-friendly techniques (distraction and instrumentation without fusion).